Making Medicine a Business X-ray Technology, Global Competition, and the Transformation of the Japanese Medical System, 1895-1945 - Donzé, Pierre-Yves (Springer Singapore, 2018)
This book goes back to the origins of the transformation of health and medicine into a business, during the first part of the twentieth century, focusing on the example of Japan. In the past hundred years, medicine has gone from being a charitable activity to a large economic sector, amounting to 12-15% of the GDP in many developed countries, and one of the fastest-growing businesses around the world. Despite the mounting presence of the medical industry, there is a lack of academic work detailing this major transformation. The objective of this book is to fill this gap and address the following question: how did medicine become a business? Using over ten years of research in the field, Pierre-Yves Donzé argues that economic factors and business factors were decisive in transforming the way that medicine enters our lives. This book will be of interest to historians of medicine, business historians, health economists, scholars in medical humanities, and more. .